Exploratory Study of Incubator Tenant Firm Social Capital through Network Analysis - Wain, J (2014)
This paper looks to explore the degree of social capital possessed by incubator tenant firms that being the resource accrued from their networks and constituent relations. It analyses how networks, and the social capital within, are leveraged to access resources and isolate which toes of networks are more important than others. Findings show that different types of networks are utilised different in terms of resource acquisition and that social capital is an important factor in this dynamic.